2020
DOI: 10.1080/13603124.2020.1770867
|View full text |Cite
|
Sign up to set email alerts
|

Educating school leaders: engaging in diverse orientations to leadership practice

Abstract: As school leadership has increased in complexity, policy makers, educationalists, and researchers have realized that principalship requires preparation. However, several researchers have called for a better understanding of how school leadership education affects the learning and activities of principals. This empirical study explores how novice principals in Sweden understand and engage in principal training and investigates their formation of identity in the interaction between school leader education and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Liljenberg and Wrethander (2020) show that participants in the SNPTP find the program's long-term focus on internship-related examining tasks challenging, but they gradually take on and learn from the tasks. Jerdborg (2022aJerdborg ( , 2021 found out that participants in the SNPTP adopt one of three separate learning identities in the educational context, each affecting both how they perceive the program and how they approach their practice. Skott and Törnsén (2018) as well as Ärlestig (2012) shared that participants' previous experiences seem to affect their learning in the program.…”
Section: Research On School Leaders' Professional Development In Educ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Liljenberg and Wrethander (2020) show that participants in the SNPTP find the program's long-term focus on internship-related examining tasks challenging, but they gradually take on and learn from the tasks. Jerdborg (2022aJerdborg ( , 2021 found out that participants in the SNPTP adopt one of three separate learning identities in the educational context, each affecting both how they perceive the program and how they approach their practice. Skott and Törnsén (2018) as well as Ärlestig (2012) shared that participants' previous experiences seem to affect their learning in the program.…”
Section: Research On School Leaders' Professional Development In Educ...mentioning
confidence: 99%
“…Accordingly, school leaders who have participated in high quality training programs, are argued to become better prepared, more consistent in how they exercise their leadership and get better at leading school development (e.g., Darling-Hammond et al, 2010). However, school leaders are found to experience, understand, and make use of the program content pertaining to such trainings rather differently in their professional practice (Darling-Hammond et al, 2010;Huber, 2013;Jerdborg, 2022a;McCulla and Degenhardt, 2016). This entails exploring the very issues for dissimilar participants as individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, principals are also tasked with student management, human resources, communication, planning, scheduling, coaching, and a broad range of other responsibilities that take time away from reflective practice. Drake (2020) and Jerdborg (2020) have suggested that educational leaders committed to growing in their practice collectively engage in critical and theoretical reflection within their current context and to extend their prior understandings. Yet, research has revealed that school leaders spend the least amount of their time on professional growth (Camburn et al, 2010;May et al, 2012).…”
Section: Cognitive Demands For Educational Leadersmentioning
confidence: 99%
“…While professional development may evoke visions of traditional learning frameworks through workshops, conferences, or courses, Drake's (2020) and Jerdborg's (2020) research highlight a critical point for school leaders as they move forward in their careers-seeking opportunities to connect critical and theoretical reflection within their current situations to extend schemata (i.e., their mental blueprints to guide future thinking and behavior). The NASSP-LPI national survey data (Levin et al, 2020) indicates that principals are leaving the field due to a lack of responsive professional development, establishing that current practices are not sufficient.…”
Section: Cognitive Demands For Educational Leadersmentioning
confidence: 99%
See 1 more Smart Citation